2016
DOI: 10.15407/tpwj2016.08.05
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of development of structural heterogeneity in the fusion zone of pearlite steel with austenitic nitrogen-containing weld metal

Abstract: The peculiar features of development of structural heterogeneity at high-temperature heating in the unstable fusion zone of the austenitic weld with the pearlite steel were considered. It was shown that one of the factors influencing the high nickel content in the weld and low heat input of welding on reduction of width of ferrite interlayer is the decrease in overheating and degradation of carbides in the HAZ metal. However, these changes do not prevent the film precipitation of carbides and embrittlement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Vishniakas [11] found that the failure of austenitic electrode welds was viscous, and individual parts were quasibrittle failures, while the failures of ferritic and pearlitic electrode welds were moderate. Elagin et al [12] found that during long-term high-temperature heating, the formation of nitride particles and grain refnement help to improve the microstructure stability of the weld, inhibit the development of carbide reactions, and reduce the microstructure inhomogeneity of the weld. Terefore, the carbides are distributed more uniformly in the fusion zone with pearlitic steel, thereby reducing the hot brittleness of dissimilar steel welds.…”
Section: Introductionmentioning
confidence: 99%
“…Vishniakas [11] found that the failure of austenitic electrode welds was viscous, and individual parts were quasibrittle failures, while the failures of ferritic and pearlitic electrode welds were moderate. Elagin et al [12] found that during long-term high-temperature heating, the formation of nitride particles and grain refnement help to improve the microstructure stability of the weld, inhibit the development of carbide reactions, and reduce the microstructure inhomogeneity of the weld. Terefore, the carbides are distributed more uniformly in the fusion zone with pearlitic steel, thereby reducing the hot brittleness of dissimilar steel welds.…”
Section: Introductionmentioning
confidence: 99%